POLA PENYELESAIAN SENGKETA KONSUMEN PADA TRANSAKSI ELEKTRONIK - Bambang Sugeng Ariadi; Zahry Vandawati Chumaida; Trisadini Prasastinah Usanti (Lex Journal: Kajian Hukum & Keadilan, 2021)
During the COVID-19 pandemic, to avoid transmission of COVID-19, the government implemented restrictions on community activities (PPKM). Social restrictions during the Corona Virus (Covid-19) pandemic encourage the use of electronic transactions to become more massive. The Covid-19 pandemic has made consumers and business actors increasingly use electronic systems in transactions. The increase in electronic transactions during the Covid-19 pandemic, adds to the risk of loss for consumers. During the pandemic, consumer complaints related to online transactions soared. This is the problem with the idea of ​​community service. For this reason, the solution given is the pattern of consumer dispute settlement patterns in electronic transactions.